Menyorot Nikah Misyār Perspektif Pemikiran Hukum Islam - Dulsukmi Kasim (Al-Mizan (e-Journal), 2019)
This article discusses about the misyār marriage as considered a model of marriage by some to be odd because it is different from the normal model of marriage that is carried out by a married couple who are Muslim in general. This type of research is descriptive qualitative which is examined by the approach of Islamic law. The results of the study show that the conditions and pillars of marriage are indeed fulfilled, the functions and responsibilities of the husband and wife continue to run normally and are not limited by time. Both parties intend and commit to perpetuating the marriage together forever. However, in practice the wife or woman is the dominant role in realizing the marriage to the point that she does not demand her husband to fulfill his basic rights after marriage later. The trigger for this marriage is the great desire of wealthy women who are financially well-established to get a mate and a place to devote affection from themselves and their children. Viewed in terms of the motivation for the marriage to take place by both parties there is no problem.